Impact of Cd concentrations on the physical properties of Cu2(CdxZn1-x)SnS4 thin films. (October 2018) - Courel, Maykel; Martinez-Ayala, A.; Sanchez, T.G.; Regalado-Perez, E.; De Los Santos, I. Montoya; Mathews, N.R.; Mathew, X.
Abstract: In this paper we are reporting an in-depth study into the material properties of cadmium incorporated kesterite material Cu2 (Cdx Zn1-x )SnS4 (CZCTS). Though it was reported in the past that CZCTS can be a candidate solar cell material, little is known about the material characteristics of this compound. In this work, the impact of Cd content on structural, morphological, optical, electrical and opto-electronic properties of CZCTS films is studied by XRD, Raman, EDXS, SEM, UV–Vis, Seebeck effect, photoconductivity, I-T, Kelvin probe, and Hall measurements. It was found that the CZCTS band-gap varies almost linearly with the Cd concentration in CZTS lattice. Photosensitivity, carrier concentration and work function showed a clear tendency with respect to Cd content. The in-depth material characterizations and in particular the electrical and opto-electronic data presented in this paper will help designing opto-electronic devices based on this material. Graphical abstract: Highlights: Phase-pure Cu2 (Cdx Zn1-x )SnS4 thin films are obtained by thermal processing. Electrical properties as a function of Cd content in the film are reported. Structural, morphological, optical and electrical properties of CZCTS film can be tailored as a function of Cd content.